Simplify:

(-2y + 6)/(-8y)

### 1 Answer | Add Yours

You need to simplify the fraction `(-2y + 6)/(-8y)` , such that:

`(-2y + 6)/(-8y) = (-2(y - 3))/(-8y)`

Reducing duplicate factors yields:

`(-2(y - 3))/(-8y) = (y - 3)/(4y)`

`(-2y + 6)/(-8y) = y/(4y) - 3/(4y)`

Reducing duplicate factors yields:

`(-2y + 6)/(-8y) = 1/4 - 3/(4y)`

**Hence, performing all possible simplifications, under the given conditions, yields **`(-2y + 6)/(-8y) = 1/4 - 3/(4y).`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes